Genetic diversity and molecular evolution of Plum bark necrosis stem pitting-associated virus from China. - Linning Qu; Hongguang Cui; Guanwei Wu; Jufang Zhou; Jiaming Su; Guoping Wang; Ni Hong (PLoS ONE, 2014)
Plum bark necrosis stem pitting-associated virus (PBNSPaV), a member of the genus Ampelovirus in the family Closteroviridae, infects different Prunus species and has a worldwide distribution. Yet the population structure and genetic diversity of the virus is still unclear. In this study, sequence analyses of a partial heat shock protein 70 homolog (HSP70h) gene and coat protein (CP) gene of PBNSPaV isolates from seven Prunus species grown in China revealed a highly divergent Chinese PBNSPaV population, sharing nucleotide similarities of 73.1-100% with HSP70h gene, and 83.9-98.6% with CP gene. Phylogenetic analysis of HSP70h and CP sequences revealed segregation of global PBNSPaV isolates into four phylo-groups (I-IV), of which two newly identified groups, II and IV, solely comprised Chinese isolates. Complete genome sequences of three PBNSPaV isolates, Pch-WH-1 and Pch-GS-3 from peaches, and Plm-WH-3 from a plum tree, were determined. The three isolates showed overall nucleotide identities of 90.0% (Pch-GS-3) and 96.4% (Pch-WH-1) with the type isolate PL186, and the lowest identity of 70.2-71.2% with isolate Nanjing. For the first time, to the best of our knowledge, we report evidence of significant recombination in the HSP70h gene of PBNSPaV variant Pch2 by using five programs implemented in RDP3; in addition, five codon positions in its CP gene (3, 8, 44, 57, and 88) were identified that appeared to be under positive selection. Collectively, these results indicate a divergent Chinese PBNSPaV population. In addition, our findings provide a foundation for elucidating the epidemiological characteristics of virus population.